High-Performance Two-Ply Yarn Supercapacitors Based on Carbon Nanotubes and Polyaniline Nanowire Arrays - Wang, Kai; Meng, Qinghai; Zhang, Yajie; Wei, Zhixiang; Miao, Menghe (Advanced materials (Weinheim), 2013)
Fine count two‐ply yarn supercapacitors are constructed from carbon nanotube yarns and polyaniline nanowires. The thread‐like supercapacitor possess excellent electrochemical capacity and are very strong and flexible. When being woven or knitted into wearable electronic devices, alone or in combination with conventional textile yarns, the two‐ply yarn supercapacitors can be flexed and stretched repeatedly without significant loss of capacitance.